Causes and Climatic Consequences of the Impact Winter at the Cretaceous‐Paleogene Boundary. Issue 3 (3rd February 2020) - Tabor, Clay R.; Bardeen, Charles G.; Otto‐Bliesner, Bette L.; Garcia, Rolando R.; Toon, Owen B.
Abstract: Prolonged periods of low light and cold temperatures at Earth's surface are hypothesized effects of the end‐Cretaceous asteroid impact. However, debate remains about the causes and consequences of this "impact winter." We perform simulations of the Chicxulub impact with an Earth system model that can simulate the evolution of extreme aerosol loading to quantify the climatic responses to emissions (soot, sulfur, and dust) associated with the impact winter. We show that all impact winter emissions can drastically reduce surface temperature and precipitation. However, only soot emission from impact‐driven firestorms is capable of reducing light to below the photosynthetic threshold for many months. Therefore, our results suggest that widespread fires may have been necessary to produce the observed pattern of marine extinction across the Cretaceous‐Paleogene boundary. We identify polar coasts and the surrounding open oceans as regions likely to have experienced the least climatic, and biotic, disruption from the impact winter. Plain Language Summary: Over 75% of all species went extinct across the Cretaceous‐Paleogene boundary (66 million years ago). This extinction coincided with a massive asteroid impact in the Yucatan Peninsula, which emitted material high into the atmosphere and potentially caused widespread fires. These emissions from the impactor, impact site, and fires would have blocked sunlight from reaching the surface, resulting in an "impact winter" that likely contributed to the mass extinction. However, details of the impact winter have been difficult to quantify. Here we use a state‐of‐the‐art Earth system model to simulate the climate responses to emission of dust and sulfur from the asteroid impact and soot from fires. We find that all simulated emission scenarios reduce sunlight at the surface, cause global cooling, and disrupt the hydrologic cycle. However, only soot emission from fires is able to reduce sunlight, and therefore prevent the growth of primary producers, for long enough to potentially starve large marine organisms. Our results suggest that widespread fires and the resulting soot emission may have been an important component of the extinction. Further, in all emission scenarios we find that the impact winter was least disruptive to the climate in the high‐latitude regions, potentially providing refugia for life. Key Points: Compared to sulfur and dust, soot emission from fires produces the largest reduction in surface light, temperature, and precipitation A prolonged reduction in surface light from soot emission could help explain the marine extinction by starvation High‐latitude coastal regions experienced the least climatic, and likely biotic, disruption from the impact winter